Организация работы транспортных средств и водителей при обслуживании логистической системы в разные периоды суток - Горяинов, Алексей Николаевич; Фомина, Я. В. (Eastern-European Journal of Enterprise Technologies, 2009)
In the article questions are represented touching problem descriptions of work of transport in the round-the-clock mode. The general chart of co-operation of basic blocks of influencing to work of transport is represented. Mathematical description of basic measures on the increase of duration of work of transport vehicles on a line is offered